The role of women in the utilization of Enhalus acoroides: livelihoods, food security, impacts and implications for coastal area management. Issue 1 (September 2020) - Nessa, N; Gatta, R; Ambo-Rappe, R; Jompa, J; Yahya, A F
Abstract: Coastal and island communities depend heavily on marine resources for their food and income. During the west monsoon (September to February), fishermen rarely go to sea, and their activities are limited to the small-scale fisheries, including gleaning the Enhalus acoroides fruits. Participants in this small-scale fishery sector are mainly women; with little or no skill required, these gleaners are often overlooked by the district level fisheries-related census. This case study focused on the role of coastal women with different levels of knowledge and utilization of E. acoroides in three cities/districts of South Sulawesi. This study aimed to determine the contribution of E. acoroides fruit collection to coastal community livelihoods and food security, to identify the impacts, and to seek alternative solutions for seagrass management. Qualitative methods were used to gather information on E. acoroides fruit collection, fishery knowledge, livelihood contributions, perceptions of seagrass condition, and alternative management solutions. Around 90% of E. acoroides fruit collectors were women aged between 30 to 80 years old. Women contribute greatly to livelihoods and food security in coastal areas because they play dominant roles in household affairs and the sale of fishery products. Unfortunately, the methods currently used for collecting E. acoroides fruit can be destructive and may have contributed to the decline in seagrass cover. However, prohibiting the collection of E. acoroides would not be an appropriate solution. A win-win solution is needed to empower women while simultaneously managing seagrass ecosystems sustainably.